Seismic behaviour of precast sandwich wall panels of steel fibre reinforced concrete layers and fibre reinforced polymer connectors - Lameiras, Rodrigo (2021)
In recent past, the authors developed an innovative modular system for low rise building made by structural sandwich panels. This system was conceived with the focus on the rationalization of the construction process and on the thermal efficiency of the building. Thus, the precast panels comprise two outer Steel Fibre Reinforced Self-Compacting Concrete (SFRSCC) layers, a thermal insulation material and Glass Fibre Reinforced Polymer (GFRP) connectors. Studies previously made by the authors have proved the viability of the proposed solution when subjected to flexural loads (out-of-plane loads). However, the in-plane biaxial cyclic behaviour of these type of panels has not yet been assessed. Therefore, to investigate the response of these panels to loading conditions that can occur in a seismic event, an experimental program was carried out. This program was composed of almost real-scale panels (2.0 m by 2.0 m), with and without openings, which were subjected to a constant vertical load representative of the load transferred by the slab to the panel, while horizontal reversed cyclic loading was imposed to the top of the panel. The in-plane cyclic behaviour of the panels was evaluated in terms of strength, stiffness, ductility and energy dissipation. The results have shown that the tested prototypes were able to withstand high values of lateral loads, namely 212 kN and 155 kN in the prototypes without and with opening, respectively.